Nationalism, globalization, and Africa - Amoah, Michael (New York : Palgrave Macmillan, 2011)
"Nationalism, especially supranationalism is the bane of global governance, and globalization. Whereas globalization seeks to unify the globe to function to advantage, supranationalisms operate to frustrate the coherence and achievement of this aim. This book delves into the theories of nationalism, the contours of supranational activity within global politics, international political economy, and global trade alliances vis-a-vis Africa. The book also identifies a list of African countries with identical issues, serial political difficulties, or time bombs ticking, and examines the performance of their political economies and new security challenges, using global indicators. "--Provided by publisher.
"Nationalism, especially supranationalism is the bane of global governance, and globalization. Whereas globalization seeks to unify the globe to function to advantage, supranationalisms operate to frustrate the coherence and achievement of this aim. This book delves into the Theories of Nationalism, the contours of supranational activity within global politics, international political economy, and global trade alliances vis-a-vis Africa. The book also identifies a list of African countries with identical issues, serial political difficulties, or time bombs ticking, and examines the performance of their political economies and new security challenges, using global indicators"--Provided by publisher.
Machine generated contents note: -- Theorizing on Nationalism * Supranationalisms and Globalization: the contours and subcontours of power and trade alliances * Global Governance and the politics of handling conflict: Sudan, Kosovo, and South Ossetia * Africa and China * Sudan, Somalia, Uganda, and Cote d'Ivoire * South Africa, Angola, Zimbabwe, and Kenya * Guinea, Gabon, Congo-Brazzaville, Cameroon, Egypt * Tanzania, Botswana, and Ghana * Union Government of Africa * International Politics of Africa.
Includes bibliographical references and index.
Keywords: Nationalism -- Africa; Globalization -- Africa; Africa -- Politics and government; Africa -- Foreign relations